Driving Waveform Design of Electrowetting Displays Based on a Reset Signal for Suppressing Charge Trapping Effect - Zhang, Taiyuan; Deng, Yong (Frontiers in Physics, 2021)
Electrowetting display (EWD) device is a new type of reflective optoelectronic equipment with paper-like display performance. Due to the oil backflow phenomenon, it is difficult for pixels to be maintained a stable aperture ratio, so the grayscale of EWDs cannot be stabilized. To reduce the oil backflow in EWDs, a driving waveform composed of a driving signal and a periodic reset signal was proposed in this paper. A direct current (DC) signal was designed as the driving signal for driving pixels. The aperture ratio of pixels was determined by the amplitude of the DC signal. The periodic reset signal was divided into a charge release phase and a driving recovery phase. During the charge release phase, the driving voltage was abruptly dropped to 0V for a period to release trapped charges. In the driving recovery phase, the driving voltage was rapidly increased from 0V to a maximum value. To reach the same grayscale of EWDs, the driving waveform was returned to the driving signal at the end of the driving recovery phase. Experimental results showed that the aperture ratio of EWDs was unchanged when the driving waveform was applied. However, the aperture ratio of pixels was gradually decreased with the conventional driving waveform. It was indicated that the charge trapping effect and the oil backflow phenomenon can be effectively inhibited by the proposed driving waveform. Compared with the conventional driving waveform, the speed of oil backflow was reduced by 90.4%. The results demonstrated that the proposed driving waveform is beneficial for the achievement of stable grayscale in EWDs.